Efficient cooling system design by using different shaped nanoparticles and rotating cylinders in channel system for photovoltaic thermal management - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Taylor & Francis Inc, 2025)
Research focusing on improving the efficiency and performance of renewable energy systems requires the development of cooling systems (CSs) with effective solutions, including photovoltaic (PV) thermal management. The current work proposes a unique cooling method that uses double rotating cylinders (RCs) and different shaped alumina nanoparticles (NP; spherical, blade, brick, and cylindrical) in water for conductive panel's cooling channel. The numerical study is performed for different values of Reynolds number (Re: 100-600), rotational Re (Rew: 0-20), size of the cylinders (Rc: 0.01H-0.2H), and solid particle volume fractions (svf: 0-0.03). It is observed that vortex size and numbers behind the cylinders can be controlled by varying Re and Rew. A 16 degrees C temperature drop of the panel is achieved at the highest Re at svf = 0.03. When rotations are active, the average Nu increases 99% and 37% for water and nanofluid (NF) at Rew = 20 and Re = 250 while temperature drops of 15 degrees C and 7.5 degrees C are obtained. The highest performance coefficient (PEC) is obtained as PEC = 1.38 when NF is used at Rew = 15. Large cylinders results in lower PEC values. When rotations are not active, the average Nu rises by about 26.8%, 13.5%, 12.8%, and 3.5% for cylindrical, blade, brick, and spherical-shaped particles while average cell temperature drops by about 5.5 degrees C, 4.5 degrees C, 4.3 degrees C, and 1 degrees C. The highest PEC value is obtained as 1.23 when cylindrical particles at the highest loading are used for stationary cylinders. Proper orthogonal-based model is considered for estimation of spatially varying panel temperature.
Keywords: Cooling channel; finite volume method; nanoparticle shape; POD; PV system; rotating cylinders